Chiropterophily syndrome in phyllostomid bats (Chiroptera, Phyllostomidae): a literature review - Êmili da Silva Piceta; Gisele Leite de Lima Primam; Gabrieli Zanette; Daniel Galiano (Revista Brasileira de Ciências Ambientais)
This review explores the relation between pollination and chiropterophily, emphasizing phyllostomid bats as key pollinators, particularly in tropical and subtropical ecosystems. These bats play an essential role in chiropterophilous pollination syndromes, where plants have evolved specific morphological traits to attract nocturnal bats. Bibliometric data show us that during the period analyzed (2004–2024), 174 scientific articles were published, and Brazil emerged as the primary contributor to scientific production on chiropterophily. Although chiropterophily syndrome provides numerous ecological and economic benefits, its study presents significant challenges due to a variety of ecological, behavioral, and methodological factors. Several analyzed manuscripts highlight the critical interdependence between bats and plants and underscore the urgent need for conservation strategies to preserve the ecological integrity and sustainability of ecosystems. A number of studies also show how changes in the phenology of plant species can compromise plant-pollinator interactions, and highlight the increasing impacts of habitat fragmentation and urbanization on bats. Our data show that, although scientific production on chiropterophily has grown in recent years, the variations observed over time may reflect changes in research priorities, funding availability, and a lack of specialized researchers in the field.